Excel Application Training for Regional Guardian Equipment and Staff and Management of Bumdes Batujonggi Kumanis Village - Khairunnisa, Khairunnisa; Iswandi, Iswandi; Putra, Fitra Kasma; Rahmi, Lidya; Niarman, Abdurrahman (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2022)
The role of technology is urgently needed by society as a precaution in dealing with the changes in the age of Industrial Revolution 4.0 to Industrial Revolution 5.0. Operating a computer, especially the Excel application, is one of the hard skills for the community. Microsoft Excel is usually known as number processing software or it can be referred to as a spreadsheet application that is designed to process data automatically such as arithmetic calculations, formulas, use of functions, tables, charts and data management to create information. This service activity presents issues identified by Kumanis Nagari officials and government, namely the lack of optimal use of computers, particularly the community's use of the Excel application, and the need to improve the community's knowledge and skills to Optimization of use to improve the Excel application. The solution offered is the training of the Excel application for processing simple data such as the data processing of official travel orders and wage data of the employees. The methodology for implementing this non-profit activity uses the Participatory Action Research (PAR) approach. The results of conducting this training are designed to provide an understanding of using the Excel application to create official travel orders and employee payroll data, as well as increase hard skills for the apparatus and staff of the village guard and management of BUMDES Batujonggi Nagari Kumanis.